Adherence to oral antineoplastic agents by cancer patients: definition and literature review. (15th September 2013) - Bassan, F.; Peter, F.; Houbre, B.; Brennstuhl, M.J.; Costantini, M.; Speyer, E.; Tarquinio, C.
<x xml:space="preserve">Abstract</x> Since the 1990s, oral chemotherapy has been gaining ground as cancer treatment. This therapy seems to have few toxic effects and offers patients good quality of life. However, in addition to the fears the therapy might generate in patients, oral treatment raises a new issue, which, until now, has been marginal in this field: therapeutic observance or adherence. We investigated the research into adherence to oral chemotherapy among cancer patients published between 1990 and July 2013. Studies showed considerable diversity in terms of both the definition and measurement of adherence. As well, adherence to antineoplastic therapy is affected by the patient's understanding of the treatment and ability to remember information provided by the physician, treatment length and psychological distress. Our review of the few studies on adherence to anticancer drug treatment raises some questions that could be pursued in future research. In light of our findings, patients should receive 'therapy education' to help them and their support groups better understand the disease and its treatment and to achieve optimal health management and improved treatment effectiveness.